Archaeological artefacts and their cataloguing: comparisons with archival practice - Hellmuth Kramberger, Anja (Atlanti +, 2025)
Purpose: Certain archaeological artefacts, depending on the definition of “what constitutes an archival document,” can be treated in accordance with the princi-ples of archival theory and practice. This article examines archaeological artefacts that bear inscriptions and are catalogued using archaeological methods and com-pares this approach with the cataloguing practices used for archival documents.Methodology: The article discusses appropriate cataloguing practices within archival science, i.e. how archival documents are recorded. A comparative meth-odology is thus proposed.Results: Through presentation and comparison, the article outlines cataloguing practices and identifies procedures that apply equally to the cataloguing of archae-ological artefacts and archival documents and highlights potential shared elements.Conclusions: The results of this research demonstrate the compatibility of cata-loguing archaeological artefacts and archival documents, opening new possibil-ities and outcomes in the context of digitization and the application of artificial intelligence.
Keywords: archaeological artefacts; archival documents; arheološki artefakti; arhivski dokumenti; cataloguing; comparison; katalogiziranje; primerjava; shared elements; skupni elementi